Блум таксономиясы инновациялық технологиясының негізінде ұйымдастырылған биология сабағы (The Journal of Psychology and Sociology, 2019)
Currently, people have no doubt that leading nation XXI century should be nation with education technology and effective education space. Head of State N.A. Nazarbayev defined education and science as strategic directions for the development and modernization of Kazakhstan. The key priorities of educational programs should be the development of abilities to continuously adapt to changes and assimilation of new knowledge. The change of the educational paradigm has led to the need to introduce innovative methods into the learning process. Important tasks of modern education are not only the formation of system knowledge, educational skills and abilities, but also the development of communication skills in the self-government educational and cognitive activities. It is necessary to understand and master new approaches to the educational process, to renew education, to take into account the age and individual psychological abilities of students. In this regard, in the teaching of biology there is a tendency to use modern methods for the development of students’ research and communication skills. In this article, teachers who are currently teaching biology disciplines are encouraged to provide information that contributes to improving the ability to comprehend and use this information to search for, analyze, and obtain information necessary for the further development of students.Key words: Bloom’s taxonomy, innovative technology, humoral regulation, Fishbone, Blob tree.